Influence of selenium-enriched yeast supplementation on biomarkers of oxidative damage and hormone status in healthy adult males: A clinical pilot study - EL-BAYOUMY, Karam; RICHIE, John P; BOYIRI, Telih; KOMNINOU, Despina; PROKOPCZYK, Bogdan; TRUSHIN, Neil; KLEINMAN, Wayne; COX, Julie; PITTMAN, Brian; COLOSIMO, Steven (Cancer epidemiology, biomarkers & prevention, 2002)
The mechanisms responsible for the protective role of selenium against the development of prostate cancer remain to be determined (L. C. Clark et al., J. Am. Med. Assoc., 276: 1957-1963, 1996). In the present study, we tested the hypothesis that selenium supplementation reduces oxidative stress. A secondary aim was to determine whether selenium-induced changes in testosterone (T) metabolism may also be involved. To this end, we conducted a double-blind, randomized, placebo-controlled trial of 247 micro g selenium/day administered p.o. in the form of Se-enriched yeast. Study subjects were 36 healthy adult males, 11 blacks and 25 whites, 19-43 years of age. Supplementation occurred over the first 9 months, after which all subjects were placed on placebo for an additional 3 months. Blood and urine were collected at baseline and after 3, 9, and 12 months. In the selenium group, plasma selenium levels were 2-fold higher than baseline values after 3 and 9 months and returned to 136% of baseline after 12 months (P < 0.0001), whereas in the placebo group, levels were unchanged. A 32% increase in blood glutathione (GSH) levels was observed after 9 months in the selenium group only (P < 0.05). This change coincided with a 26% decrease in protein-bound GSH (bGSH) and a 44% decrease in bGSH:GSH ratios (P < 0.05). The changes in GSH and bGSH were highly correlated with changes in plasma selenium concentrations and may reflect a decrease in oxidative stress. No changes were observed in either group for plasma T, dihydrotestosterone (DHT) or DHT:T ratios, suggesting that selenium had no effect on the alpha-reductase involved in the conversion of T to DHT. A small but significant decrease in prostate-specific antigen levels was observed after 3 and 9 months (P < 0.001), and this difference disappeared after 12 months. Future trials will test the above hypothesis in prostate cancer patients and in subjects at high risk for prostate cancer.